TEN IMAGES OF MODERATION THROUGH PROPHETIC SUNNAH (Islamic Sciences Journal, 2023)
The issue of moderation is one of the important matters surrounding a, person, whether in or outside his home or at the work, with people or with the student, So, you find people and those who are righteous working and dealing with every thing in moderation, excluding excess and injustice and without injustice or weakness, but it may be in the art of dealing with Cases is despised and imitating the messenger of Allah, Allah blessing and peace upon the prophet Mohammed.